Integrin αIIbβ3 Activation and Clustering in Minimal Synthetic Cells. Issue 4 (20th February 2022) - Benk, Lucia T.; Benk, Amelie S.; Lira, Rafael B.; Cavalcanti-Adam, Elisabetta Ada; Dimova, Rumiana; Lipowsky, Reinhard; Geiger, Benjamin; Spatz, Joachim P.
Abstract : Platelet adhesion and activation are mediated by integrin αIIb β3 clustering, which is crucial for the hemostatic function of platelets. In an activated state, integrins provide the connection between the extracellular matrix and the actin cytoskeleton through a variety of cytoplasmic proteins, such as talin. Here, droplet‐based microfluidics is applied to generate cell‐sized giant unilamellar vesicles (GUVs) with a defined molecular composition to quantify the adhesion of integrin αIIb β3 ‐containing protocells in relation to the number of integrin–talin head domain (THD) complexes. Furthermore, it is shown that THD induces integrin clustering in protocells adhering to fibrinogen. The formation of this molecular link, which has, so far, only been observed in vivo, is an essential step in synthetic cell design to recapitulate integrin‐mediated bidirectional signaling across the membrane. These results pave the way for further quantitative investigations of protein–protein interactions between integrins and associated proteins and their assembly within such defined, but complex, synthetic cells. An essential future step to mimic the complex interaction between cells and their environment will be to combine synthetic approaches with peptide chemistry to guide the molecular mechanisms involved in integrin binding and activation. Abstract : Integrin αIIb β3 ‐containing giant unilamellar vesicles (GUVs) generated by droplet‐based microfluidics with a defined molecular composition allow the quantification of their adhesion to fibrinogen‐coated surfaces in relation to the number of integrin–talin head domain(THD) complexes. Furthermore, the induction of integrin clustering at the adhesion area by THD is shown for the first time for a synthetic cell system.